Prevalence, antibiogram, and risk factors of methicillin-resistant Staphylococcus aureus (MRSA) asymptomatic carriage in Africa: a systematic review and meta-analysis - Ahmed Azzam; Heba Khaled; Heba Mohamed Fayed; Youssef Mansour; Mariam Eldalil; Eslam Elshennawy; Haitham Salem; Hoda A. Elkatan (BMC Infectious Diseases)
Abstract Background MRSA represents a significant public health challenge, particularly in resource-constrained regions like Africa. A critical factor in its spread is the role of asymptomatic carriers, who not only facilitate transmission but also face a markedly higher risk of developing MRSA-related infections. Against this backdrop, the current meta-analysis provides a comprehensive evaluation of MRSA colonization rates, associated risk factors, and antibiotic resistance profiles across African populations. Methods A comprehensive literature search was conducted across African Journals Online, African Index Medicus, PubMed, Scopus, Google Scholar, and Web of Science from January 1, 2014, to January 1, 2025. Eligible studies reported on MRSA colonization rates, associated risk factors, or antibiotic resistance patterns within African populations. Results were presented as pooled prevalence or risk ratios (RR) with 95% confidence intervals, employing a random-effects model in R software (meta package). A p-value of < 0.05 was considered statistically significant. The study followed the PRISMA guidelines throughout. Results Sixty-nine studies with 23,484 participants from 16 African countries were included. Subgroup analyses identified Healthcare Workers and hospitalized patients as having the highest pooled prevalence at 13.6% and 12.9%, respectively. Conversely, lower prevalence rates were observed among healthy community residents and children, at 4.1% and 4.7%, respectively. Among HCWs, Egypt reported the highest MRSA colonization rate at 18.1%. Key risk factors for MRSA colonization include a history of hospitalization (RR: 2.2), prior antibiotic use (RR: 1.4), diabetes mellitus (RR: 4.4), HIV with CD4 < 200 cells/µL (RR: 2.8), invasive procedures (RR: 4.8), and being a nurse compared to a physician (RR: 1.8), all with p < 0.05. Antibiotic resistance of MRSA was low for linezolid (2.7%) and vancomycin (5.9%), but higher for mupirocin (10.7%), clindamycin (23.6%), and Trimethoprim/sulfamethoxazole (38.9%). Conclusion MRSA colonization is a significant public health challenge in Africa, particularly among healthcare workers and hospitalized patients. Implementing targeted interventions for these high-risk groups can effectively reduce MRSA transmission and overall infection burden. Continuous monitoring is essential, especially given the resistance to mupirocin, a key antibiotic used for MRSA decolonization.